Experimental investigation of two-phase thermosyphon loop for passive containment cooling. (5th February 2021) - Yin, Xuan; Hu, Jian; Chi, Xiangyu; Li, Yaru; Nan, Zezhao; Wang, Naihua
Highlights: Boiling intensity has a more significant impact under low heat transfer rate. Heat transfer capacity is limited by the length of two-phase fluid region. The higher the filling ratio, the higher the pressure required for circulation. Heat transfer behavior includes convective heat transfer and nucleate boiling. Abstract: This article investigates the operating characteristics of a two-phase thermosyphon loop in a pressure vessel to simulate the operating state of the thermosyphon loop in a passive containment cooling system. In this study, water is used as the working fluid, and the filling ratio ranges from 40% to 65%. The condenser is placed in a boiling water tank at 100 °C. The evaporator is placed in a pressure vessel, and the experimental range of pressure in the vessel is 0.32–0.46 MPa. The effects of the filling ratio and vessel pressure on the circulation loop and evaporator are analyzed, and the thermal resistance is calculated to characterize the heat transfer performance. The results show that the driven temperature difference and the length of the two-phase fluid region in the evaporator tube determine the heat transfer capacity of the thermosyphon loop. As the vessel pressure increased, a high filling ratio resulted in better heat transfer. However, the higher the filling ratio, the higher the pressure required for circulation, and the greater the pressure loss along the circulation path. The convective heat transfer and nucleate boiling heat transfer occur simultaneously in the evaporator at low heat flux.